Design and performance in the first flight of the transition radiation detector and charge detector of the CREAM balloon instrument - Patrick Allison; H. S. Ahn; K. C. Kim; Gabriele Bigongiari; Paolo Maestro; O. Ganel; Jung-Suk Han; P. S. Marrocchesi; J. K. Lee; S. Coutu; N. B. Conklin; P. J. Boyle; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2007)
Abstract The Cosmic Ray Energetics And Mass (CREAM) instrument flew on a high altitude balloon in Antarctica in 2004–2005 for a record breaking 42 days. An array of detectors was deployed to identify cosmic rays and measure their energies up to several hundred TeV. A major science goal is the measurement of secondary nuclei at high energy (produced by spallation reactions of heavier cosmic rays in the interstellar medium). This is done with a transition radiation detector using xenon-filled proportional tubes, and charge identification devices comprising plastic scintillator and Cherenkov counters. Accurate and stable performance of these detectors is necessary for the reliable identification of the secondary nuclei. The design of these detectors and their performance in flight are discussed, and preliminary data presented.